Management and outcome of post-traumatic cerebrospinal fluid rhinorrhea - Ismail, Nasiru Jinjiri; Lasseini, Ali; Koko, Aliyu Muhammad; Shehu, Bello Bala (International Journal of Research in Medical Sciences, 2020)
Background: Post-traumatic cerebrospinal fluid (CSF) rhinorrhea are relatively uncommon neurosurgical condition that is associated with serious morbidity and life-threatening complications like meningitis. As such, it requires prompt and thorough evaluation and treatment. Is of note that, only few studies discussed CSF rhinorrhea in literature especially in sub-Saharan Africa. This study was designed to report outcomes of management of post-traumatic CSF rhinorrhea seen in our institution. Methods: Relevant data of all patients with post-traumatic CSF rhinorrhea managed from July 2015 to June 2019 were retrospectively reviewed. Results: Out of the total 1942 cases of head injury managed over the study period 20 cases (1%) were diagnosed with CSF rhinorrhea. The mean age of presentation was 30.5 years. All patients were male and road traffic accidents was the only aetiological factor noted. Majority of patients developed rhinorrhea after 48 hours of injury (12/20). Pneumocephalus was the commonest computerised tomographic scan finding and about 2/3rd of the patients required operative treatment by transcranial anterior cranial fossa repair (13/20). The remaining patients were managed non-operatively with acetazolamide, antihistamines, stool softeners and antibiotics. The outcome was generally good with no recurrence noted. The rate of mortality was 10% (2/20) and resulted from meningitis. Conclusions: Posttraumatic CSF rhinorrhea was seen in 1% of cases of head injury in our environment and affects males predominantly. Although, the outcome of treatments was good, 10% mortality caused by meningitis was recorded.